Interprofessional Collaboration in the Detection of and Early Intervention in Child Maltreatment: Employees' Experiences - Jaana Inkilä; Aune Flinck; Tiina Luukkaala; Päivi Åstedt-Kurki; Eija Paavilainen (Nursing Research and Practice)
Child maltreatment is a global problem and a multidimensional phenomenon occurring in all social classes. This study depicts interprofessional collaboration associated with the detection of and early intervention in child maltreatment taking place in the family. The data were collected in a large Finnish city, Tampere (207 866 citizens). A survey was administered to employees in day care, basic education, social and health services, and police (n=865). The results indicate that interprofessional collaboration associated with the detection of and intervention in child maltreatment was best accomplished by social service employees and police personnel. Employees in day care, basic education, health services, and police had little knowledge of the methods used in other units. The most support for collaboration was reported by employees in social services and day care. The results provide basic knowledge of interprofessional collaboration associated with child maltreatment between the agencies involved in the study. The research evidence can also be utilized in an international context when developing collaboration between different fields.